You & Your Aquarium : The Complete Guide to Collecting And Keeping Aquarium Fishes - Mills, Dick (London Dorling Kindersley Ltd, 1995)
A practical guide to the care of aquarium fishes. It offers information on various aspects of keeping your fishes healthy, well-fed and in good condition.
Including Illustrations, Appendix and Index
Keywords: Aquariums -- Aquarium fishes